Daratumumab-Based Second Line Therapy Improves Outcomes after VRD Induction, Upfront Autologous Transplant and Lenalidomide Maintenance - Pasvolsky, Oren; Milton, Denai R.; Tanner, Mark R.; Bashir, Qaiser; Srour, Samer A.; Saini, Neeraj Y.; Lin, Paul; Siddiqui, Umer R.; Khan, Hina N.; Haider, Asad A.; Ramdial, Jeremy L.; Nieto, Yago; et al. (Transplantation and cellular therapy, 2025)
For eligible patients with newly-diagnosed multiple myeloma (MM), induction therapy with bortezomib, lenalidomide and dexamethasone (VRD) followed by autologous transplant (autoHCT) and lenalidomide (Len) maintenance is generally the most commonly used treatment approach. However, there are scarce data on second line (2L) treatment approaches following the disease progression. Retrospective single-center study of MM patients with first progression after receiving VRD induction, upfront autoHCT between 2005-2021, and single-agent Len maintenance. Primary outcome was second progression-free survival (PFS2), computed from the date of start of 2L regimen to the date of second disease progression or death, or the last follow-up date. Secondary outcomes included overall survival (OS) and response rates. 146 patients were included, with a median age of 60 years (range 32-80); 27% had high-risk cytogenetics. Single-agent melphalan was used for conditioning for most patients (88%). Prior to transplant, 58% patients achieved ≥VGPR (Table 1). At first post-transplant progression, 31% (n=45) received an IMiD+ PI – containing triplet as a 2L regimen, 24% (n=35) received a daratumumab (Dara)-based regimen (33/35 triplet regimen with IMID/PI and dexamethasone) and 21% (n=30) received IMiD/PI – containing doublet. Patients who received Dara-based 2L regimens had higher rates of ≥ VGPR (63%) at best response, compared to those who received other regimens: IMiD+PI – containing triplet (35%), and IMiD/PI – containing doublet (34%) (p=0.001). After a median follow-up of 35.8 months from the first progression, median PFS2 and OS of the entire cohort were 12.4 months (95% CI 10.2-16.9) and 52.6 months (95% CI 45.0-86.3), respectively (Figure 1). For patients who received Dara-based 2L regimens, the median PFS2 was 59.9 months (95% CI 12.4 – not reached), and for those who received IMID+PI doublet or triplet 2L regimens the median PFS2 was 12.3 months (95% CI 5.5-34.3) and 11.5 (95% CI 6.7-19.3), respectively (p=0.001) (Figure 2). In multivariable analysis, use of Dara-containing 2L regimens was associated with better PFS2 (HR 0.35, p<0.001), whereas having clinical (vs. biochemical) first progression was associated with worse PFS2 (HR 1.58, p=0.026). Progression after ≥ 12 months from autoHCT (vs. <12 months) was associated with better OS in multivariable analysis (HR 0.23, p<0.001). Use of busulfan+melphalan -based conditioning (HR 4.06, p<0.001) and having clinical (vs. biochemical) first progression (HR 1.99, p=0.006) were associated with worse OS. In a cohort of patients who received VRD induction, autoHCT followed by Len maintenance and then had first progression, median PFS2 was approximately 12 months and median OS was < 4.5 years. Patients receiving a Dara-based 2L regimens had a better PFS2 that lasted almost 5 years.